Sao Tome and Principe : Request for a Three-Year Arrangement Under the Poverty Reduction and Growth Facility. - International Monetary Fund. (Washington, D.C. : International Monetary Fund, 2005)
This paper reviews the request from the Sao Tome and Principe authorities for a Three-Year Arrangement Under the Poverty Reduction and Growth Facility (PRGF). In 2004, the economy continued to grow at a moderate pace, but inflation increased to 15 percent by year-end, as bank credit to the private sector rose sharply and the government loosened fiscal policy. The proposed program for 2005-07 aims at correcting macroeconomic imbalances and sets the conditions for sustained strong growth. Real GDP growth is envisaged to slow down in 2005 in response to tight financial policies.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet